2013
DOI: 10.4238/2013.august.29.4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new locus conferring antixenosis to the brown planthopper in rice cultivar Swarnalata (Oryza sativa L.)

Abstract: ABSTRACT. The brown planthopper [Nilaparvata lugens (Stål); BPH] has caused severe damage to rice production. The identification of resistance genes and the development of BPH-resistant varieties are economical and effective ways to manage this pest. Using an F 2 population from a cross between the Indica cultivars 93-11 and Swarnalata, we mapped the Qbph-8 locus to a 7.3-cM region on chromosome 8 in two tests, flanked by the markers RM339 and RM515. In this population, Qbph-8 explained 7.7 and 6.6% of the phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…BR4831 is a dual-gene ( Bph14 and Bph15 ) homozygous stable line, while C602 and HF106 are single-gene ( Bph14 or Bph15 ) homozygous lines, and BR4831 showed higher resistance to BPH than HF106 and C602 in both the seed box and field tests. Employing seed box tests, several previous studies involving the Bph14 and Bph15 genes [ 11 – 16 , 26 ] as well other genes [ 19 , 27 ] have demonstrated similar results regarding pyramided rice lines showing stronger resistance than single-gene lines. The antibiosis recorded herein with the two single-gene introgression lines C602 and HF106 was not as strong as that reported by Li et al [ 11 ], where 92.3% of Bph14 single-introgression lines exhibited moderate resistance, and all of the Bph15 single-introgression lines showed resistance or high resistance in the seed box test.…”
Section: Discussionmentioning
confidence: 62%
“…BR4831 is a dual-gene ( Bph14 and Bph15 ) homozygous stable line, while C602 and HF106 are single-gene ( Bph14 or Bph15 ) homozygous lines, and BR4831 showed higher resistance to BPH than HF106 and C602 in both the seed box and field tests. Employing seed box tests, several previous studies involving the Bph14 and Bph15 genes [ 11 – 16 , 26 ] as well other genes [ 19 , 27 ] have demonstrated similar results regarding pyramided rice lines showing stronger resistance than single-gene lines. The antibiosis recorded herein with the two single-gene introgression lines C602 and HF106 was not as strong as that reported by Li et al [ 11 ], where 92.3% of Bph14 single-introgression lines exhibited moderate resistance, and all of the Bph15 single-introgression lines showed resistance or high resistance in the seed box test.…”
Section: Discussionmentioning
confidence: 62%
“…Antixenosis refers to plants that can avoid pest-related damage. Qiu et al [28] detected one antixenotic QTL, Qbph8 ( t ), from resistance variety Swarnalata which conferred a host preference behavior.. Tolerance refers to plants being able to sustain tissue loss with little or no decrease in fitness relative to that in the undamaged state [24, 32].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it should be beneficial for controlling BPH outbreaks. Previous studies have indicated that rice cultivars containing major and minor genes/QTLs have a stronger antixenosis compared to plants containing a single gene/QTL [28]. Furthermore, it also confers more durable resistance to the BPH insects [5, 39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, antibiosis resistance is conferred against the biology of the insect (Heinrichs 1986). The major impacts of antibiosis are weakened persistence of insects and lowered rate of reproduction and growth followed by host tissue (Panda and Heinrichs 1983;Kennedy et al 1987;Qiu et al 2013).…”
Section: )mentioning
confidence: 99%